Phage display-derived ligands provide structural insight into insulin-like growth factor I function. Issue 2 (2004) - Skelton Skelton, Nicholas J. Nicholas J.; Schaffer Schaffer, Michelle L. Michelle L.; Deshayes Deshayes, Kurt Kurt; Blandl Blandl, Tamas Tamas; Runyon Runyon, Steven Steven; Nakamura Nakamura, Gerald Gerald; Sidhu Sidhu, Sachdev S. Sachdev S.
Abstract : Insulin–like growth factor–I (IGF–I) is a central mediator of cell growth, differentiation and metabolism. Structural characterization of the protein has been hampered by a combination of internal dynamics and self–association that prevent crystallization and produce broad NMR resonances. To better characterize the functions of IGF–I, we have used phage display to identify peptides that antagonize the binding of IGF–I to its plasma binding proteins (IGFBPs) and cell–surface receptor (IGF–R). Interestingly, binding of peptide improves dramatically the quality of the NMR resonances of IGF–I, and enables the use of triple–resonance NMR methods to characterize the complexes. One such peptide, designated IGF–F1–1, has been studied in detail. In the complex, the peptide retains the same loop–helix motif seen in the free state whilst IGF–I contains three helices, as has been seen previously in low–resolution structures in the absence of ligand. The peptide binds at a hydrophobic patch between helix 1 and 3, a site identified previously by mutagenesis as a contact site for IGFBP1. Thus, antagonism of IGFBP1 binding exhibited by the peptide occurs by a simple steric occlusion mechanism. Antagonism of IGF–R binding may also be explained by a similar mechanism if receptor binding occurs by a two–site process, as has been postulated for insulin binding to its receptor. Comparisons with crystallographic structures determined for IGF–I in other complexes suggest that the region around helix 1 of IGF–I is conformationally conserved whereas the region around helix 3 adopts several different ligand–induced conformations. The ligand–induced structural variability of helix 3 appears to be a common feature across the insulin super–family. In the case of IGF–I, exchange between such conformations may be the source of the dynamic nature of free IGF–I, and likely has functional significance for the ability of IGF–I to recognize two signaling receptors and six binding proteins with high affinity.